“Uncovered in the glass cages”. Rethinking neoliberal governance in the times of COVID-19: Critical performativity for performance management in higher education: - Seyama, S. M. (South African Journal of Higher Education, 2022)
This conceptual article draws on social harm theory and critical management studies to critically examine the neoliberal governance of academics’ performance management in higher education, particularly in the emerging “normal” of COVID-19. The article argues that the COVID-19 pandemic has created a crisis that lays bare the deleterious global ramifications of the dominant political-economic ideology of neoliberalism in every aspect of societal life, more so in education. Moreover, the justifiably lauded shift to the digital space of teaching and learning is increasing the already problematic panoptic surveillance and is invading the hiding spaces within the glass cages. The neoliberal approach to PM is inflicting social harms, unintentionally and intentionally. With the COVID-19 pandemic offering us the “rega” moment of opportunity to rethink and pragmatically insert critical alternatives to the neoliberal governance of universities’ performance management practices, this article proposes a critical performativity approach to work towards incremental micro-emancipations.